The Impact of Macroeconomic Variables on Actuarial Premium Calculation: Evidence from Indonesian Life Insurance Using OLS Regression - Alim Jaizul Wahid; Khandker Farid Uddin Ahmed; Renda Sandi Saputra (Research Collaboration Community (RCC), 2026)
Actuarial science requires accurate net premium calculations, yet traditional approaches often ignore macroeconomic dynamics such as inflation and interest rates. This study investigates the impact of macroeconomic variables specifically inflation rate and Bank Indonesia reference interest rate (BI Rate) on actuarial net premium calculations for term life insurance products in Indonesia. Using annual time-series data from 2005 to 2023, this study applies Ordinary Least Squares (OLS) regression to quantify the relationship between macroeconomic indicators and net premium values computed using the Indonesian Mortality Table (TMI-2019). The results indicate that inflation has a significant positive effect on net premium values, while the BI Rate exerts a significant negative effect, consistent with actuarial theory regarding the present-value discounting mechanism. The adjusted R-squared value of 0.847 confirms strong explanatory power of the model. These findings provide practical guidance for insurance companies and the Financial Services Authority (OJK) in setting premium reserves under dynamic macroeconomic conditions. This study contributes to the intersection of actuarial science and macroeconomic modeling, which remains underexplored in the Indonesian context.